Association Between Oral Pathogens in Infectious Endocarditis and Myocardial Infarction Risk - Gani, Azhari (Dentistry Faculty, 2023)
Background: This study investigated the association between infectious endocarditis caused by oral pathogens and an increased risk of myocardial infarction. The primary focus is on how oral pathogens, such as Streptococcus viridans and Staphylococcus aureus, commonly found in the oral flora, can enter the bloodstream and contribute to the development of infective endocarditis. Objective: This study aims to highlight the importance of oral health as an important aspect in preventing cardiovascular disease, especially for individuals with a history of heart valve disease or other cardiovascular risk factors. Methods: This study investigates how this pathogen attaches to damaged or abnormal heart valves, causing inflammation and further damage, which can lead to embolism formation. These emboli have the potential to block blood flow to the heart, causing ischemia and triggering myocardial infarction. The study also explored the role of inflammation and the immune response to infection in increasing the risk of arterial plaque formation and thrombosis. Results: The study found that these oral pathogens can enter the bloodstream through dental procedures or poor oral health conditions and attach to damaged or abnormal heart valves. This attachment causes inflammation and damage to the valve and the formation of emboli, which can move to the heart and block the coronary arteries. The result is an increased risk of ischemia and myocardial infarction, highlighting the importance of good oral health and effective cardiovascular risk management to prevent these heart health complications. Conclusion: Streptococcus viridans can enter the bloodstream and attach to damaged heart valves, causing inflammation and embolism formation that has the potential to block blood flow to the heart, causing ischemia and increasing the risk of heart attack and related cardiovascular complications.